ENHANCEMENT OF SENSITIVITY, DETECTION RANGE, AND DETECTION LIMIT USING GA METHOD POTENTIOMETRIC BIOSENSOR WITH UREASE ENZYME IMMOBILIZATION TECHNIQUE ON PVA - Sibarani, Willi Firmando; S, Abd Hakim (EINSTEIN (e-Journal), 2024)
This study aims to increase the sensitivity range of the width of the UV-Vis absorbance peak with Glutaraldehyde (GA) crosslinking and useful to determine the level of urea in the urine. The potentiometer cell consists of an indicator electrode and a reference electrode. The indicator electrode is denoted PVA-Enzyme/GA/PVC-KTpCIPB, meaning PVA-Enzim as the first layer, GA as the second layer and PVC-KTpCIPB as the third layer. Biosensor with urease enzyme immobilization technique analyzed variations of urea 10-7-10-1 M. The potentiometric method of the biosensor detects signal and voltage (potentiometer cell). The signals that were analyzed for signal variables were symmetrical up and down signals of 2000 signals/second. Voltage was carried out by linear curve analysis, the results of linear curve analysis were the range of detection from a concentration of 10-4-10-2 M with cross-linked GA which increased the absorbance, the detection limit was 10-4 M, the sensitivity was 46.67 mV/ war reversibly and R squared (R2) which is 0.9839 is close to linear.